Compositions, flavour and antiradical properties of products from subcritical water treatment of raw Isada krill. (3rd May 2015) - Koomyart, Intira; Nagamizu, Hironori; Khuwijitjaru, Pramote; Kobayashi, Takashi; Shiga, Hirokazu; Yoshii, Hidefumi; Adachi, Shuji
Summary Comparative analysis of subcritical water (SCW) treatment and ambient pressure boiling one of raw Isada krill was performed for the nutritive, flavour and antiradical properties of krill extracts and residues as well as the molecular mass and odour intensity of the extract. SCW treatment was performed for 10 min in a batch‐type vessel in the temperature range of 100–240 °C, using a 1:1 weight ratio of raw krill to water. Higher protein and lipid contents were obtained by SCW treatment relative to boiling. The lipid content of the SCW extracts increased with increasing treatment temperature. Protein was the main component in these extracts, and the highest protein content was achieved by SCW treatment at 200 °C. High‐molecular‐mass species decomposed under SCW treatment at high temperatures with consequent generation of smaller molecules. The antiradical activity of the SCW extract, determined by DPPH and ABTS assays, increased with increasing treatment temperature. The krill extracts and residues exhibited shrimp‐like flavour, and the most desirable flavour was obtained by SCW treatment at 140 °C or 160 °C for 10 min. The treatment would be applicable for the production of seasonings from Isada krill.